2010
DOI: 10.1111/j.1469-8986.2010.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a deficit in volitional action generation in patients with obsessive‐compulsive disorder

Abstract: Obsessive-compulsive disorder (OCD) patients show deficits in tasks of executive functioning like the antisaccade (AS) task. These deficits suggest problems in response inhibition or volitional saccade generation. Thirty patients (15 nonmedicated) and 30 healthy subjects performed antisaccades and simple volitional saccades (SVS), that is, centrally cued saccades. In SVS, two aspects of volitional saccade generation were disentangled: response selection and initiation. Latencies of OCD patients were increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
0
14
1
3
Order By: Relevance
“…In line with previous studies, latencies and within‐subject variability of latencies in the prosaccade task, which served as a control task of basic oculomotor function, were intact in patients and first‐degree relatives (Jaafari et al, ; Kloft et al, ). In contrast to previous reports (Kloft et al, ), neither patients nor relatives showed impairments in the performance of volitional saccades compared to healthy controls. There was no difference regarding within‐subject variability of volitional saccade latencies, and the examination of mean amplitudes of prosaccades and volitional saccades did not yield any differences between the three groups.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In line with previous studies, latencies and within‐subject variability of latencies in the prosaccade task, which served as a control task of basic oculomotor function, were intact in patients and first‐degree relatives (Jaafari et al, ; Kloft et al, ). In contrast to previous reports (Kloft et al, ), neither patients nor relatives showed impairments in the performance of volitional saccades compared to healthy controls. There was no difference regarding within‐subject variability of volitional saccade latencies, and the examination of mean amplitudes of prosaccades and volitional saccades did not yield any differences between the three groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the lack of replication cannot be accounted for by lack of statistical power, as the groups of patients and controls were five times larger in the present investigation than in the previous study (Kloft et al, ; n = 22 for each of the three groups), and the sample of relatives was approximately 50% larger. Power analyses using G*Power (Faul, Erdfelder, Lang, & Buchner, ) indicated that there was a power of > 99% to detect effects of the same sizes as reported by Kloft et al (). Alongside the large sample size, notable strengths of the present study include the thorough clinical characterization of subjects as well as the consideration of several covariates and moderating variables, such as symptom dimensions, medication, comorbidity, and age.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Maruff, Purcell, Tyler, Pantelis, and Currie () showed that patients with OCD had no difference in mean RT of visually guided saccades compared to controls, while their mean RT increased significantly when they were asked to produce volitional saccades such as antisaccades and internally triggered saccades. Kloft, Kischkel, Kathmann, and Reuter () also showed an increase in mean RT for internally triggered saccades for patients with OCD, although they did not confirm a difference from controls for mean RT of antisaccades. In our previous study, all patients with schizophrenia that were tested were receiving antipsychotic medication.…”
mentioning
confidence: 92%
“…Il s'agit le plus souvent de pathologies neurologiques, comme la maladie de Parkinson, les tics, le syndrome de Gilles de la Tourette ou encore certains types d'épilepsie [13]. En psychiatrie, des atteintes de la volition ont été mises en évidence dans le trouble obsessionnel compulsif [14], dans certains troubles du contrôle des impulsions [15] et dans la schizophrénie [16] où des voies neurales motrices des ganglions cortico-basaux [17] seraient altérées. Sur le plan neurobiologique, les pathologies dites « volitionelles » partageraient une forme d'altération du contrôle du comportement qui serait en lien avec des anomalies de l'axe dopaminergique [18].…”
Section: Principales Fonctions Cognitives Impliquéesunclassified